Visible goods, personality traits and preferences for status: New evidence for Uruguay - Martín Leites; Gonzalo Salas; Andrea Vigorito (Desarrollo y Sociedad)
The identification of positional goods is crucial for understanding how social interactions motivate consumption decisions. Drawing on micro-data from the Estudio Longitudinal del Bienestar en Uruguay (ELBU), we identify a list of visible goods and assess whether their visibility varies according to respondents’ characteristics. We find that expenditure on automobiles, jewelry and watches, clothing, and personal care rank at the top of the scale. The expenditure visibility index does not significantly vary across socio-economic groups but exhibits a positive and significant association with conscientiousness. Individuals who report a higher propensity to compare themselves with others are more likely to notice third parties’ expenditures on visible goods. Preferences for status and personality traits also provide complementary information about expenditure visibility, with considerably greater effects in the former case. Our findings may contribute to explaining a substantial portion of the observed heterogeneity in consumer choices.